2023
DOI: 10.1039/d3qo00902e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of unprecedented sesquiterpenes with distinctive ring skeletons from Daphne aurantiaca employing an integrated strategy

Abstract: Guaiane-type sesquiterpenoids are well-known in medicinal chemistry of natural products, but the unprecedented sesquiterpenoid scaffold furnished by forming unexpected carbon-carbon linkages or occurring startling cracking deserves expected to be further...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Our efforts to determine the relative stereochemistry of C-6′ were unsuccessful because of the conformation flexibility of C-6′ and the long distance between C-6′ and C-2′ and 3′. Therefore, the calculated NMR chemical shifts of two possible diastereomers 8a and 8b were subjected to custom DP4+ analysis with the experimental values. , The statistical results indicated the structural equivalence of 8 and 8b (100% probability). The specific rotation of (2′ R , 3′ R , 6′ S )- 8 was calculated as +40.9; from a comparison of the experimental value of 8 [[α] D 20 +36.0 (c 1.00, MeOH)], the absolute configuration of 8 was determined to be 2′ R , 3′ R , 6′ S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our efforts to determine the relative stereochemistry of C-6′ were unsuccessful because of the conformation flexibility of C-6′ and the long distance between C-6′ and C-2′ and 3′. Therefore, the calculated NMR chemical shifts of two possible diastereomers 8a and 8b were subjected to custom DP4+ analysis with the experimental values. , The statistical results indicated the structural equivalence of 8 and 8b (100% probability). The specific rotation of (2′ R , 3′ R , 6′ S )- 8 was calculated as +40.9; from a comparison of the experimental value of 8 [[α] D 20 +36.0 (c 1.00, MeOH)], the absolute configuration of 8 was determined to be 2′ R , 3′ R , 6′ S .…”
Section: Resultsmentioning
confidence: 99%
“…The conformers with a Boltzmann population of over 1% were further geometry optimized at the B3LYP/6-31G­(d) level, and subsequently, the Gauge-Independent Atomic Orbital (GIAO) calculations of magnetic shielding tensors were accomplished by DFT at the mPW1PW91/6-311+G­(d,p) level with the PCM model in the Gaussian 09 package. The OR values were calculated using Gaussian 09 by the time-dependent density functional theory method at the b3lyp/tzvp level in MeOH, of which the given wavelength was 589.3 nm. …”
Section: Methodsmentioning
confidence: 99%
“…Intermediates Ia and Ib might undergo alkene isomerization [11] and oxidative cleavage of the C-4/5 bond to produce diketo intermediates IIa andIIb [32] , from which vital intermediatesIIIa and IIIb could be formed through selective keto-enol tautomerism, reduction, and oxidative cleavage. IIIa andIIIb were then transformed into the crucial intermediatesIVa and IVb by a aldol condensation [33] to furnish the bicyclo[3.3.1]nonane core. Moreover, IVa andIVb were likely transformed to intermediates Va andVb by redox reaction [34] , which would undergo esterification to finally generate (-)-2 and (+)-2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that daphaulides A 10 and E 11 , from Daphne aurantiaca , are also derived from cleaved guaiane sesquiterpenoid precursors. 9 …”
mentioning
confidence: 99%